Compositional determinants of fruit and vegetable quality and nutritional value - Vicente, Ariel R.; Manganaris, George A.; Darre, Magalí; Ortiz, Cristian M.; Sozzi, Gabriel O.; Crisosto, Carlos H. (My University, 2021)
The dietary constituents obtained from fruits vegetables include water, fiber, proteins (legumes), sometimes fats (olive, avocado, and nuts), minerals, and digestible carbohydrates. Starch-based staples, such as potato, cassava, corn, banana, and plantain, provide a major energy source in several regions, being particularly important dietary sources in developing countries. Fruits and vegetables are the main dietary source of vitamin C and a significant source of provitamin A and vitamin B6. Compared to other food sources, they are high in potassium and low in sodium. Ascorbic acid (AsA) in horticultural commodities may enhance the bioavailability of dietary iron. Fruits and vegetables are low in calories (excluding staple crops) and are cholesterol-free. They also include a variety of nonnutritive bioactive phytochemicals (phytosterols, carotenoids such as lycopene, AsA, tocopherols, glucosinolates, thiosulfinates, and phenolics) that may help to prevent disease incidence. This has led to the current recommendation that healthful diets include a variety of fresh horticultural commodities. Despite efforts made in the last decade, in the United States, only 1 in 10 adults eat enough fruits or vegetables. This chapter provides an overview of the composition and nutritional properties of fruits and vegetables.
Keywords: Fruits; vegetables; nutrition; antioxidants; composition; fiber; vitamins; minerals; bioactive; phytonutrients